A study on the perceptual relevance of crosstalk equations for stereoscopic displays. Issue 6 (24th August 2013) - Xia, Zhenping; Li, Xiaohua; Cui, Yuan; Chen, Lei; Teunissen, Kees
Abstract: Although several crosstalk definitions have been proposed to indicate the level of crosstalk in stereoscopic displays, they do not necessarily correlate with perceived crosstalk. Based on two perception experiments, with each a different approach, we studied the correspondence between 10 objective crosstalk equations and perceived crosstalk. The first experiment, in which the crosstalk level was evaluated, demonstrates that crosstalk equations based on Weber's law (Δ L / L ) show the highest correlation with perceived crosstalk for the most critical case, that is, a center circle in an outer disc. A second experiment, based on crosstalk visibility thresholds, supported that crosstalk equations based on Weber's law show the highest correspondence with human perception.